A kinematic analysis of the CO clouds toward a reflection nebula NGC 2023 observed using the Nobeyama 45 m telescope: Further evidence for a cloud–cloud collision in the Orion region. (28th June 2021) - Yamada, Rin I; Enokiya, Rei; Sano, Hidetoshi; Fujita, Shinji; Kohno, Mikito; Tsutsumi, Daichi; Nishimura, Atsushi; Tachihara, Kengo; Fukui, Yasuo
Abstract: We performed fully sampled J = 1–0 line observations of 12 CO and 13 CO toward the reflection nebula NGC 2023 using the Nobeyama 45 m telescope. It covered the entire NGC 2023 region with angular and velocity resolutions of 19″ corresponding to 0.04 pc and 0.33 km s −1, respectively. We analyzed the data focusing on gas dynamics and revealed two velocity components, each with a mass of $\sim\! 3000 \mbox{$\, M_\odot $}$, at radial velocities of 10 and 12 km s −1 . These components show spatially complementary distributions and are connected in velocity, both of which are the typical signatures of cloud–cloud collision (CCC). Although previous studies favored a scheme of triggering by the H ii region of IC 434, our results show that the effect of the H ii region is limited only to the surface of the molecular cloud, and does not contribute to the entire gas compression and the overall star formation. Comparing the present results with those for neighboring NGC 2024, we find that their active star formation can be explained by a single CCC event. We suggest that the 10 and 12 km s −1 clouds collided ∼0.4 Myr ago, which is common to the regions, but triggered the B1.5V-type star HD 37903 as well as ∼20 low-mass stars in NGC 2023, and ∼20 OB stars in NGC 2024. The column density in NGC 2023 is two to three times lower than that of NGC 2024, which may result in the different star formation activity suggested by the trend of ∼50 other CCC-triggered star-forming regions in the literature.